Exploring the Role of Ayurvedic Garbhini Paricharya in Healthy Pregnancy Outcomes (AYUSHDHARA, 2025)
Garbhini Paricharya is a crucial component of Ayurveda that prioritizes the comprehensive well-being of expectant mothers through carefully structured dietary practices, lifestyle modifications, and various therapeutic approaches. This review investigates the importance of Ayurvedic principles in fostering the health of both mothers and their unborn children. By analyzing established Ayurvedic literature alongside modern research findings, the article emphasizes the benefits of Garbhini Paricharya in facilitating a healthy pregnancy, minimizing the risk of complications, and promoting seamless labor and delivery. A systematic application of these Ayurvedic guidelines can lead to a more balanced pregnancy journey, alleviating prevalent issues such as nausea, fatigue, and complications during childbirth. The care methodology in Ayurveda places significant emphasis on trimester-specific dietary plans, the incorporation of herbal supplements, and beneficial lifestyle practices, including yoga and meditation. Combining these Ayurvedic strategies with contemporary obstetric care could significantly enhance maternal health by addressing nutritional needs, alleviating stress, and improving outcomes for the fetus. The review also delves into the role of Panchakarma therapies, the importance of mental health, and how a mother’s well-being influences fetal development. Additionally, it discusses the necessity of regulatory frameworks for Ayurvedic pregnancy care, ethical considerations surrounding herbal medicine, and the future research potential in this domain. By integrating Ayurvedic practices with modern medical techniques, a holistic prenatal care model can be developed, ensuring optimal results for both mothers and their children. This review seeks to present a well-researched evaluation of Ayurvedic pregnancy care and its applicability in today's maternal health landscape.